Analisis Pendekatan Adaptif: Studi Literatur Untuk Kemandirian Anak Autis Ringan Melalui Peran Aktif Orang Tua - Wike Afsari Sinaga; Fitri Handayani Chaniago; Shafira Rahma Dina Sinaga; Amanda Olivia Munthe; Rivandi Anju Gurning; Anggia Puteri (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
Adaptive approach is an intervention strategy that places the unique needs of each child with mild autism as the center of attention, so that learning and therapy methods are flexibly adjusted to individual characteristics and abilities. This literature review examines how adaptive approach can increase the independence of children with mild autism through the active role of parents and the implementation of structured daily activities. Parents act as the main partners in the learning process, not only providing emotional support, but also becoming facilitators who help children apply the skills learned at school into everyday life at home. Structured daily activities provide clear and consistent routines, helping children understand and anticipate activities, thereby reducing anxiety and increasing focus in carrying out tasks. Stimulus-response techniques are an effective method in developing children's adaptive behavior, with positive reinforcement that motivates children to continue learning and repeating independent behavior. Close collaboration between teachers, therapists, and parents creates an adaptive and consistent learning environment, which allows children to develop independence gradually and sustainably. This study confirms that holistic interventions involving full support from parents and the implementation of structured daily activities are the keys to success in increasing the independence of children with mild autism.